A new species of Polypedates (Anura: Rhacophoridae) from the Western Ghats, India, allied to the Sri Lankan P. cruciger Blyth, 1852 - Das, I.; Ravichandran, M.S. (Centre for Herpetology, Madras Crocodile Bank Trust, 1998)
A new species of polypedates is described from Southern Tamil Nadu State, south-western India. The new species, P.pseudocruciger is closely related to P.cruciger Blyth, 1852, from the mid hills and low country of Sri Lanka, from which it can be diffrentiated in showing a obtuse cutaneous spur on heel (vs absent); skin of forehead free (vs co-ossified to the fronto-pariental and squamosal bones); toe I webbing between distal and distal, subarticular tubercles; and tympanum diameter over 80 (vs less than 65) per cent diameter of orbit.